AICCRA fosters foresight analysis community of practice in West and Central Africa - Segnon, Alcade (2024)
Responding to CORAF demand, AICCRA capacity development, including a foresight training toolkit, has catalyzed and capacitated a CORAF-led regional foresight Community of Practice (CoP) —12 experts (50% women), from 9 countries in West and Central Africa. CoP members mainstreamed the acquired knowledge/skills within their respective institutions to: (i) support innovative strategic planning and policy formulation, (ii) support the development of a foresight-informed regional preparedness and response plan for climate-change driven pest and disease outbreak management, and (iii) applied foresight analysis to inform the Gender component of Cameroon’s updated National Strategic Plan.